Milestones of Hematopoietic Stem Cell Transplantation – From First Human Studies to Current Developments - Juric, Mateja Kralj; Ghimire, Sakhila; Ogonek, Justyna; Weissinger, Eva M.; Holler, Ernst; van Rood, Jon J.; Oudshoorn, Machteld; Dickinson, Anne; Greinix, Hildegard T. (Frontiers in Immunology, 2016)
Since the early beginnings, in the 1950’s, hematopoietic stem cell transplantation (HSCT) has become an established curative treatment for an increasing number of patients with life-threatening hematological, oncological, hereditary and immunological diseases. This has become possible due to worldwide efforts of preclinical and clinical research focusing on issues of transplant immunology, reduction of transplant-associated morbidity and mortality and efficient malignant disease eradication. The latter has been accomplished by potent graft-versus-leukemia effector cells contained in the stem cell graft. Exciting insights into the genetics of the human leukocyte antigen (HLA) system allowed improved donor selection , including HLA-identical related and unrelated donors. Besides bone marrow (BM) other stem cell sources like G-CSF-mobilized peripheral blood stem cells and cord blood stem cells have been established in clinical routine. Use of reduced-intensity or non-myeloablative conditioning regimens has been associated with a marked reduction of non-hematological toxicities and eventually, non-relapse mortality allowing older patients and individuals with comorbidities to undergo allogeneic HSCT and to benefit from graft-versus-leukemia or anti-tumour effects. Whereas in the early years malignant disease eradication by high-dose chemotherapy or radiotherapy was the ultimate goal, nowadays allogeneic HSCT has been recognized as cellular immunotherapy relying prominently on immune mechanisms and to a lesser extent on non-specific direct cellular toxicity. This chapter will summarise the key milestones of HSCT and introduce current developments.